OPTIMIZED DELIVERY OF DICLOFENAC SODIUM FORMULATED IN A SUSTAINED RELEASE RAPHIA AFRICANA HYDROCOLLOID MATRIX - Adedokun, Musiliu; Nkanta, Clement (International Journal of Applied Pharmaceutics, 2018)
Objective: The aim of this research work was to comparatively study various proportions of a natural hydrocolloid-Raphia africana, and polyvinylpyrrolidone (PVP) as release sustaining agents in diclofenac sodium tablet formulation. Methods: The purified hydrocolloid (R. africana) was characterized by evaluating its organoleptic, physicochemical and flow properties. Diclofenac-polymer ratios of 1:0, 1:0.2, 1:0.4, 1:0.6, and 1:0.8 were employed to produce different granule batches using wet granulation method (that is, the drug was formulated with 0, 5, 10, 15 and 20 % w/w of either R. africana hydrocolloid or PVP, and coded DWB-00, DRA-05, DRA-10, DRA-15, DRA-20, DPP-05, DPP-10, DPP-15 and DPP-20, respectively). Flow properties of granules were studied by determining bulk density, tapped density, Carr's index, and Hausner's ratio for all the formulations. Compressed tablets were evaluated using various parameters as weight variation, friability, hardness, tablet thickness and diameter, content uniformity and in vitro dissolution evaluated in phosphate buffer (pH 7.3). Results: Flowability, mechanical and release parameters determined were within pharmacopoeial limits. Generally, the values of bulk and tapped densities increase as binder concentrations increase for both PVP and R. africana hydrocolloid. The values were significantly different across the batches (p<0.05). Hardness values obtained varied significantly (p<0.05) and were between 5 and 12 KgF which imply that most of the tablet batches are harder than normal depending on the proportion of the polymer used. All the batches exhibited friability within the standard limit without significant difference in values (p>0.05), indicating that tablet formulated with the experimental binders would not undergo surface abrasion. All the formulations exhibited zero order kinetics except batches DPP-10 and DPP-15 which showed Higuchi mechanism. Formulation batches DRA-05 and DRA-10 showed maximum drug release of 98% and 95% respectively after 6 h. A prolonged drug release was observed on increasing polymer ratio. Significantly higher release rates (p<0.05) were observed in the tablets formulated with PVP than those containing R. africana gum. All the batches followed non-fickian diffusion release mechanism. Conclusion: From the study, purified R. africana hydrocolloid generally appeared to perform better than PVP as sustained release agent.